Introduction to Aircraft Aeroelasticity and Loads. - Wright, Jan R. (Aerospace Series., 2014)
Introduction to Aircraft Aeroelasticity and Loads, Second Edition is an updated new edition offering comprehensive coverage of the main principles of aircraft aeroelasticity and loads. For ease of reference, the book is divided into three parts and begins by reviewing the underlying disciplines of vibrations, aerodynamics, loads and control, and then goes on to describe simplified models to illustrate aeroelastic behaviour and aircraft response and loads for the flexible aircraft before introducing some more advanced methodologies. Finally, it explains how industrial certification requirement.